Environmental Sciences, asked by Garth, 1 year ago

In a ∆ABC prove that

4(\frac{s}{a} -1 ) (\frac{s}{b} -1 ) ( \frac{s}{c}-1) = \frac{r}{R}

Answers

Answered by sahildhande987
0

\huge{\underline{\mathfrak{\blue{Answer}}}}

Formulas

\implies∆²=s(s-a)(s-b)(s-c)

\implies r = \dfrac{\triangle}{s}

SoluTion

 4 \bigg(\dfrac{s-a}{a} \bigg) \bigg(\dfrac{s-b}{b} \bigg) \bigg( \dfrac{s-c}{c} \bigg)

Multiplying S in numerator and denominator

 \dfrac{4 s(s-a)(s-b)(s-c)}{s\: abc}

 \implies\dfrac{ \cancel{4} \cancel{\triangle} ^2}{s  \cance{4} R \cancel{\triangle}}

\implies \dfrac{ \triangle}{ sR} \\ \\ \implies \boxed{\dfrac{r}{R} }

Answered by Anonymous
41

Question

In a ∆ABC prove that

4(\frac{s}{a} -1 ) (\frac{s}{b} -1 ) ( \frac{s}{c}-1) = \frac{r}{R}

Answer

refer to the attachment

hope it helps you

Attachments:
Similar questions